Networking in Spanish schools: Lights and shadows - Cecilia María Azorín Abellán (Universidad Complutense de Madrid, 2021)
Networking is an effective school improvement method that can raise collective efficacy, student outcomes, and provide more collaborative scenarios. The forms collaboration and networking take in the Spanish education system are reviewed in this article, as well as how policy and practice are providing a framework for the development of networks. Spain is presented as an example of country that is exploring the possibilities offered by networks in education. There is an updated corpus of studies that support collaborative networking in Spanish education system. The article summaries evidence of networking in seven autonomous communities (Galicia, País Vasco, Cataluña, Madrid, Valencia, Murcia and Andalucía) where there are alliances formed to implement collaboration actions among the participants, as part of research supported by projects, regulations, programs and initiatives of diverse natures. These proposals are changing the paradigm from isolation to collaboration, an alternative way of seeing education that is growing not just in policy, but also in theory and practice, so enabling illustrative examples and advances in this field of knowledge, and allowing the reader to get closer to the polyhedral dimension that networking is adopting in this particular country. There is no doubt that the arrival of collaboration networks in Spain has sparked intense debates about its “lights and shadows”. Among the lights are the increase of school-community link; the growth of the extended education approach; the effective use of resources as well as the exchange of knowledge and experiences; and greater inclusion. On the other hand, some shadows are related to the different networks’ structures; isolation, not only by teachers as individuals, but also between schools and institutions or agents, and the pressure to increase standards in a collaborative versus competitive environment.